Hodgkin’s lymphoma: post- autologous transplantation consolidation therapy - Merli, Francesco; Ballerini, Filippo; Botto, Barbara; Gotti, Manuel; Pavone, Vincenzo; Pulsoni, Alessandro; Stefani, Pietro Maria; Massaro, Fulvio; Viviani, Simonetta (Acta Biomedica Atenei Parmensis, 2020)
A first-line chemotherapy program based on the ABVD regimen is currently considered the golden standard by most hematologists, being able to achieve a cure without any need of subsequent therapies in >70% of patients with advanced-stage Hodgkin’s lymphoma (HL). To increase this percentage, efforts in recent decades focused on the development of new therapeutic strategies. A first major effort was the introduction of the BEACOPP chemotherapy regimen, which is able to increase the response rate and to reduce the need of salvage therapies. However, this result did not demonstrate an advantage in terms of overall survival compared to ABVD, mainly due to an excess of non lymphoma-related events in the follow-up phase. Here we describe three clinical cases of young HL patients who had relapsed/refractory disease after the induction chemotherapy. These three clinical cases provide practical and real world evidence in favor of the use of BV in monotherapy as consolidation treatment after autologous stem cells transplantation in patients with relapsed/refractory HL.